Heating and heat-dependent mechanical characteristics of CNT-embedded cementitious composites. (February 2016) - Kim, G.M.; Naeem, Faizan; Kim, H.K.; Lee, H.K.
Abstract: Cementitious composites incorporated with CNT were developed in the present study as a self-heating element, and heating and heat-dependent mechanical characteristics of the composites were investigated. Silica fume and poly-carboxylic acid based superplasticizer were used as dispersion agents for the CNT particles to ensure a certain electrical resistivity value that is required to induce heat generation capability in the composites. The amount of CNT added to the composites and the input voltages were varied from 0.1 wt% to 2.0 wt% and from 3 V to 20 V, respectively. A cyclic self-heating test was conducted to investigate the stability in the heat generation capability and electrical resistivity of the composites. Moreover, compressive strength and TG/DTA tests were conducted to investigate the heat-dependent mechanical properties and the amount of hydration products of the cyclically heated composites. The test results showed that the heat generation capability of the CNT-embedded cementitious composites was improved with an increase in the amount of CNT and the composites having CNT less than 0.6 wt% is appropriate as a heating element.